Influencing factors in non-vaccination during national vaccination days in Colombia (Colombia Medica, 1986)
A case-control study was carried out to identify factors associated with non-immunization during the National Immunization Journeys (NIJ) in Colombia in 1984. A previous sample representative of the whole country was the frame of reference for selecting study subjects. All the 54 cases found in the sample eligible during the NIJ but received no immunization during that period were interviewed. Similarly, 61 controls, randomly chosen among children of the sample that had received the full schedule of immunization during the NIJ, were interviewed. Significant differences with a relative risk of 3 or greater were found in a number of years of school attendance by the father, absence of radio or TV sets, inappropriate garbage, and sewage disposal, inadequate water supply, time needed to go to the immunization post, negative opinion of the father, lack of perception of the NIJ and lack of knowledge about the efficacy of immunizations related to the NIJ. Around 31% of the nonimmunized children cases could be attributed to administrative problems in the organization of the NIJ.